Psycho-pedagogical bases of preparing of the future special technology teacher - Журба, Галина (Pedagogy of Higher and Secondary Education, 2014)
Zhurba G. Р. Psycho-pedagogical bases of preparing of the future special technology teacher. Under present conditions it can not be treated only as training students in forming a system of knowledge, skills and abilities. Forming the motivational sphere of students is done by understanding the target set, taking into account not only the students on the importance of the training material for the study of other topics of the course, but also for future professional activities, selection of interesting, attractive content for students, providing professional orientation of the content and more.